“Seeing and Being Seen”: Analysis of Foucault’s View of Power Gaze - Han, Lefei (Transactions on Social Science, Education and Humanities Research, 2023)
In Foucault’s academic pedigree, gaze, as a visual tool, helps to build a power-knowledge network and promote dynamic power. The power mechanism system of modern society is Foucault’s focus: crazy people are regarded as the existence opposite to “rational people” by psychiatric diagnosis and treatment, which tries to standardize their behavior through the “medical gaze”. Panoramic open prison controls prisoners’ behaviors through invisible gaze and trains prisoners as a link to improve power reproduction. Such a gaze mode has become a universal operation mechanism in modern society. Foucault then applied gaze power to the field of painting art, which reveals a picture in the power network, that is, the traditional gaze mode of “seeing and being seen” between the viewer and the picture can be subverted through the ingenious arrangement of plane composition, light, and viewer position. In his later years, Foucault analyzed the possibility of modern people resisting the power gaze and proposed to purify their spiritual realm under the existing system by “free practice” such as criticism and self-care.